Correlation Between Intrinsic Capacity and Muscle Strength and Quality in Older Patients with Cardiovascular Disease: A Cross-Sectional Study - Yu X; Wu D; Li F; Qiao W; Chen X (Clinical Interventions in Aging)
Xiyan Yu,1,* Difei Wu,2,* Fangzhou Li,3 Wei Qiao,4 Xujiao Chen3 1The Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Geriatrics, the First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China; 4The First Department of Health Care, China-Japan Friendship Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xujiao Chen, Department of Geriatrics, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310003, People’s Republic of China, Email lily197459@163.com Wei Qiao, The First Department of Health Care, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China, Email viviqiao601@sina.comBackground: Cardiovascular disease (CVD) has become the leading cause of death worldwide. High muscle mass can reduce the incidence and mortality of CVD. In recent years, increasing attention has been given to the relationship between intrinsic capacity (IC) and CVD. This study aims to explore the relationship between the decline of IC, muscle strength, and muscle quality in older patients with CVD, providing a new method and basis for early recognition of IC decline in the older adults.Methods: This cross-sectional study included 475 older individuals from communities in Zhejiang. General data were collected, and a comprehensive geriatric assessment (CGA) was conducted. Participants with CVD were divided into three groups: IC retention, IC impairment, and IC significantly impaired. Bioelectrical impedance analysis (BIA) measurements were completed. Student’s t-test or non-parametric tests (Mann–Whitney) were used to analyze the correlation between IC and muscle-related indicators. The best cutoff values were obtained using ROC curve analysis.Results: Compared to non-CVD patients, CVD patients were older, more educated, and had higher rates of polypharmacy and comorbidity. IC decreased more significantly in CVD patients. Age (P=0.001), Fried (P=0.024), and GDS-5 (P=0.002) increased with the severity of IC decline. ADL (P=0.002), MMSE (P=0.000), MNA-SF (P=0.000), SARC-Calf (P=0.026), waist circumference (P=0.037), and muscle quality (P=0.010) decreased with the decline in IC. When IC decreased, the cutoff values for hand grip strength, waist circumference, and muscle quality were 25.45 kg, 72.55 cm, and 3.05, respectively. When IC decreased significantly, the cutoff values were 17.15 kg, 71.55 cm, and 2.28, respectively.Conclusion: The results of this study showed that in patients with CVD, the hand grip strength and muscle quality of patients with IC injury were lower than those of patients with IC retention.Keywords: CVD, intrinsic capacity, muscle quality